Enhanced durability of an iridium-bipyridine complex embedded into organosilica nanotubes for water oxidation. Issue 29 (17th July 2017) - Zhang, Shengbo; Wang, Hua; Li, Mei; Han, Jinyu; Inagaki, Shinji; Liu, Xiao
Abstract : Robust bipyridine-incorporated organosilica nanotubes were used to fabricate heterogeneous iridium-bipyridine catalysts, which showed enhanced durability in the water oxidation reaction, benefiting from the stable nanotube structures as well as the isolated active sites. Abstract : Heterogeneous metal complex catalysts for the water oxidation reaction have ever been desired for the development of devices simulating photosynthesis. This paper describes the design of highly active and robust heterogeneous iridium complex catalysts for chemical water oxidation. The heterogeneous catalyst (Ir-BPy-NT) was prepared by the post-synthetic metalation of bipyridine-containing mesoporous organosilica nanotubes (BPy-NT) with an [IrCp*Cl(μ-Cl)]2 (Cp* = η 5 -pentamethylcyclopentadienyl) complex. The as-prepared Ir-BPy-NT catalyst showed enhanced durability with high reaction activity compared to the analogous homogeneous and the conventional heterogeneous ones, due to the stable nanotube structures as well as the isolated active sites. The unique one-dimensional nanotubes with large pore diameters can also reduce the diffusion limitation and facilitate the transport of reactants and products during reactions.